2022
DOI: 10.7759/cureus.21024
|View full text |Cite
|
Sign up to set email alerts
|

Mini Nutritional Assessment (MNA) as a Reliable Tool for Nutritional Assessment of Hemodialysis Patients: A Single-Center Observation

Abstract: In this study, we evaluated mini nutritional assessment (MNA) as a tool for the assessment of the nutritional status of end-stage renal disease (ESRD) patients on maintenance hemodialysis (MHD). MethodsThis prospective cross-sectional study was done from February 2021 till August 2021 on ESRD patients on MHD at our center. Nutritional status was assessed by using MNA score which evaluates four different aspects: anthropometric measures (body mass index [BMI], weight loss, mid-arm and mid-calf circumferences); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Table (1) showed that there were significant differences (p ≤ 0.03 and JHE, Volume, 34, April (2), Copyrights @ Faculty of Home Economics Menoufia University, Shibin El Kom, Egypt 0.003) among all groups in age and weight, while there was no significant difference (p>0.05) between groups in height (cm). Besides that, there was no significant difference (P> 0.05) between overweight and obese patient in age.…”
Section: Resultsmentioning
confidence: 93%
“…Table (1) showed that there were significant differences (p ≤ 0.03 and JHE, Volume, 34, April (2), Copyrights @ Faculty of Home Economics Menoufia University, Shibin El Kom, Egypt 0.003) among all groups in age and weight, while there was no significant difference (p>0.05) between groups in height (cm). Besides that, there was no significant difference (P> 0.05) between overweight and obese patient in age.…”
Section: Resultsmentioning
confidence: 93%
“…CKD is a significant global health issue that affects more than 109.9 million individuals in developed countries and 387.5 million people in the developing world. This number is expected to rise further in the coming years [ 2 ]. Worldwide, it contributed to 956,000 fatalities in 2013, up from 409,000 in 1990 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%